The peculiarities of the genre of political and historical novels in the work of Graeme Green - Boltabayeva , Ma’rifat (The Lingua Spectrum, 2025)
This article describes the events in Graham Greene’s novels that take place in colonial countries, while the conflict in anti-colonial novels is sharply dramatic; events are often hierarchical. The novels depict the growing discontent of colonial peoples and countries and their eventual transformation into a struggle. In addition, the image of Alden Pyle in Graham Greene’s novel "The Quiet American"; the image of Winthrop Eliot in Norman Lewis’s novel "Volcanoes Over Our Heads" is described.